Proceedings of the 4th Padang International Conference on Education, Economics, Business and Accounting (PICEEBA-2 2019) 2020
DOI: 10.2991/aebmr.k.200305.147
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electronic Word of Mouth and Service Quality on Satisafaction: Destination Image as a Mediator

Abstract: The purpose of this study is to examine the relationships among electronic Word of mouth (eWOM), service quality, brand image, and satisfaction in tourism industry. The questionnaire was distributed to 80 respondents who had experience with social media online. The research data and hypothesis are analyzed by using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The findings show that eWOM has a positive influence on brand image and satisfaction. In addition, the results also find the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Hotel image (HI) is one of the constructs that is often used as a mediator that influences loyalty behavior and preferences of the customers (Bashir et al, 2020;Nurhidayati, 2020;Supardin et al, 2018). Because the research population of this study is the customers of IJCHM 34,11 hotels, not social media, the appropriate hypothesis is that the image of the social media associated with a destination hotel is not a direct contributor to the decision to stay at the hotel.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hotel image (HI) is one of the constructs that is often used as a mediator that influences loyalty behavior and preferences of the customers (Bashir et al, 2020;Nurhidayati, 2020;Supardin et al, 2018). Because the research population of this study is the customers of IJCHM 34,11 hotels, not social media, the appropriate hypothesis is that the image of the social media associated with a destination hotel is not a direct contributor to the decision to stay at the hotel.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Han and Hyun (2017) and Lai (2019) found that customers set expectations regarding service quality before any visit just through official and unofficial information sources. Nurhidayati (2020) proposed that electronic word-of-mouth (eWOM) is a strong contributor that helps to form customer expectations of service quality. Therefore, this study proposes that the image of a hotel positively contributes to ASQ:…”
Section: Hypothesis Developmentmentioning
confidence: 99%